Marital Satisfaction, Anxiety, and Health-Related Quality of Life in Myocardial Infarction Patients - Devi Wulandari (Journal of Global Pharma Technology, 2020)
Anxiety is predictor of cardiac incidents and mortality, its relationship with Health-Related Quality of Life (HRQL) remains unclear, especially in married couples, yet a marital relationship as part of the immediate environment that can be a source of support or stress. The objective of this study is to shed light on the relationship between anxiety and HRQL by adding marital satisfaction as an independent predictor and moderator. A cross-sectional study was conducted on 214 myocardial infarction patients. The patients completed three questionnaires (McNew Health-Related Quality of Life, Couple Satisfaction Index, Cardiac Anxiety Questionnaire), analysed using a four-step moderated hierarchical multiple regression. In conclusion, anxiety and marital satisfaction significantly predict patients’ HRQL. There were no significant interaction effects between anxiety and marital satisfaction in predicting HRQL. These findings could spur further research in addressing the limitations of this study and similar studies, which in turn may direct future policies in healthcare.